2019
DOI: 10.1177/2325967119861038
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Glenohumeral Instability Related to Sporting Activities Using the FEDS (Frequency, Etiology, Direction, and Severity) Classification System: A Multicenter Analysis

Abstract: Background: Glenohumeral instability is common in athletes. There are an estimated 0.12 episodes of instability per 1000 sporting exposures. Instability can lead to time away from sport and an increased risk of shoulder arthritis. Purpose: To determine the prevalence, demographic data, anatomic features, and likelihood of surgery for the different types of instability as defined by the FEDS (frequency, etiology, direction, and severity) classification system for different sports. Study Design: Cohort study; Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…Sports-related instability was also reported to be higher among males by Wagstrom et al. 3 in their study that examined glenohumeral instability in athletes. The data concluded that there was a 4.0 to 1.0 male-to-female ratio in regard to experiencing glenohumeral instability.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Sports-related instability was also reported to be higher among males by Wagstrom et al. 3 in their study that examined glenohumeral instability in athletes. The data concluded that there was a 4.0 to 1.0 male-to-female ratio in regard to experiencing glenohumeral instability.…”
Section: Discussionmentioning
confidence: 81%
“…The data concluded that there was a 4.0 to 1.0 male-to-female ratio in regard to experiencing glenohumeral instability. 3 The most common sports in which glenohumeral instability was seen were football, wrestling and basketball, and it was reported that nearly all cases were the result of trauma. 3 The findings that males are more likely to sustain recurrence due to sport is interesting when looking at the time it takes males and females to return to sport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Collision sports have also been highly associated with shoulder instability, showing a high recurrence rate among athletes in this field of sports. 7,8 Treatment of shoulder instability includes administration of anti-inflammatory medications, corticosteroid injections, physical therapy, and surgery. Among these treatment modalities, physical therapy is commonly preferred for elderly and bedridden patients, whereas surgery is recommended when patients have traumatic instability or a highly active lifestyle, or when patients have continued symptoms for more than 6 months despite physical therapy.…”
Section: Introductionmentioning
confidence: 99%